Ultrastructure of the leaf surface in species of genera Kalanchoe Adanson (Crassulaceae) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
This article provides detailed study of ultrastructure of leaves, using light and scanning electron microscopy. The ultrastructure of the surface lamina K. marnieriana (Bryophyllum section) is significantly different from the other studied species section of Kalanchoe (epicuticular type of wax, the type of terrain, no pubescence). Belonging K. eriophylla to the section Kalanchoe or Bryophyllum causes debate. According to the results of our research ultrastructure of leaf surface in this species is similar to species of Kalanchoe section. In general, species of Kalanchoe section are characterized by well-developed pubescence.
Keywords: SEM, epidermis, trichomes, stomatal apparatus.